Coronary Arteries: Normal Anatomy With Historical Notes and Embryology of Main Stems - Thiene, Gaetano; Frescura, Carla; Padalino, Massimo; Basso, Cristina; Rizzo, Stefania (Frontiers in Cardiovascular Medicine, 2021)
Anatomy of subepicardial coronary arteries became a topic of investigation at autopsy in Florence (Italy) by Banchi in the early 20th century, with the discovery of dominant and balanced patterns. Thereafter, in the 60’s of the same century Baroldi in Milan did post-mortem injection with spectacular three-dimensional casts. Later Sones at the Cleveland Clinic introduced selective coronary arteriography for in vivo visualization of coronary arteries. In the present chapter we show these patterns, as well as normal variants of origin and course with questionable risk of ischemia, like myocardial bridge as well as origin of the left circumflex coronary artery from the right with retroaortic course. As far as embryology, the coronary arteries and veins are epicardial in origin and finally connect the former with the aorta, and the latter with the sinus venosus. At the time of spongy myocardium, intramural blood supply derives directly by the ventricular cavity, whereas later, at the time of myocardial compaction, vascularization originates from the subepicardial network. The connection of the subepicardial plexus with the aorta occurs with prongs of the peritruncal ring, which penetrate the facing aortic sinuses. Septation of truncus arteriosus is not responsible for the final position of the coronary orifices. Infact in transposition of the great arteries coronary ostia are regularly located within facing sinuses of the anterior aorta.